Pengantar Etika Psikologis Buddhisme - Tjhin Kindella Yunia (Humanitas (Jurnal Psikologi), 2022)
The maritime kingdom of Srivijaya in its heyday not only controlled the world's spice trade routes, but also became the center of education and the spread of Buddhism in highly developed Southeast Asia. Buddhism gradually disappeared in the archipelago with the fall of the Majapahit kingdom, but left traces of relics to this day, such as historical sites, language and culture. Through literature study using interpretive descriptive method in this paper, the author would like to reintroduce the teachings of Buddha, especially from the psychological and ethical point of view, based on the Tipitaka Canon Pali scriptures. The psychological ethics of Buddhism is contained in the Abhidhamma Pitaka which is the third collection of Buddhist scriptures. Man in the Buddhist view is a psychophysical combination of mind (nāma) and matter/body (rūpa). Mind is a combination of consciousness (citta) and mental factors (cetasika), this combination is a variety of states of mind. There are 121 kinds of consciousness, 52 kinds of mental factors and 28 material elements, according to the ethics are classified into good, bad and neutral, but explained from a psychological point of view, most of them are psychological data analysis. Awareness is the originator of one's speech and behavior, good awareness can trigger good speech and behavior, and vice versa. The human personality is conditioned and maintained by the activity of consciousness and its effects, one's character is also determined by consciousness. The psychology of Buddhism has been integrated with modern western psychology, which is called "Conjunctive Psychology". The interdependent process of the psycho-physical functioning of the human personality, is a very important process in the psycho-therapeutic method of Buddhism..